2020
DOI: 10.3347/kjp.2020.58.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Exosomes from Dendritic Cells Stimulated with Toxoplasma gondii Lysates in Ocularly Immunized Mice

Abstract: Immunogenicity of dendritic cell-derived exosomes stimulated with <i>Toxoplasma gondii</i> lysates (TLA exo), mixed with cholera toxin as an adjuvant, was investigated in mice immunized via 2 mucosal routes (ocular vs intranasal). BALB/c mice were injected 3 times with TLA exo vaccine at 2 week interval, and the levels of IgG in serum and IgA in tear, saliva, feces, and vaginal wash were measured. To observe the expression of <i>T. gondii</i>-specific B1 gene, mice infected with ME49 &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Regarding vaccines, Gutierrez et al [143] showed that EVs from the interaction between blood trypomastigotes and bone marrow-derived DCs confer partial protection in animals challenged with lethal T. cruzi infection. These results, together with reports on other pathogens such as Toxoplasma gondii [144,145], Eimeria spp. [146], and Leishmania major [147], place EVs as promising therapeutic agents against infectious diseases.…”
Section: Preference or Restriction To A Certain Host Tissue? Factors ...supporting
confidence: 84%
“…Regarding vaccines, Gutierrez et al [143] showed that EVs from the interaction between blood trypomastigotes and bone marrow-derived DCs confer partial protection in animals challenged with lethal T. cruzi infection. These results, together with reports on other pathogens such as Toxoplasma gondii [144,145], Eimeria spp. [146], and Leishmania major [147], place EVs as promising therapeutic agents against infectious diseases.…”
Section: Preference or Restriction To A Certain Host Tissue? Factors ...supporting
confidence: 84%
“…Tumor-derived EVs stimulate antitumor immunogenicity in DCs ( André et al., 2002 ) and more interestingly, Ag-pulsed DC derived exosomes display prophylactic and therapeutic properties in tumour-bearing mice ( Zitvogel et al., 1998 ). Immune protective response triggered by EVs from Ag-loaded DCs has also been described for different pathogens such as Toxoplasma gondii ( Aline et al., 2004 ; Jung et al., 2020 ), Eimeria spp. ( del Cacho et al., 2012 ) and Leishmania major ( Schnitzer et al., 2010 ).…”
Section: Introductionmentioning
confidence: 92%
“…Toxoplasmosis, a globally prevalent zoonosis caused by Toxoplasma gondii, relies primarily on live, attenuated tachyzoites for veterinary immunization ( 110 ). A recent study reported that EVs derived from dendritic cells stimulated with T. gondii lysate elicited protective mucosal and hormonal immune responses against Toxoplasma infection in an animal model ( 111 ). Similarly, a study on Eimeria tenella , the parasite of avian coccidiosis, using exosomes from antigen-loaded dendritic cells showed a protective effect on chickens ( 112 ), suggesting the potential of EVs as a protective vaccine production.…”
Section: Extracellular Vesicles As Vaccinesmentioning
confidence: 99%